Personality, pathology and mindsets: part 1 – agency, personality and mindscapes. Issue 1 (2014) - Maurice Yolles; Gerhard Fink
<x xml:space="preserve"> Abstract </x> Purpose – This paper aims to develop a new socio‐cognitive theory of the normative personality of a plural agency like, for instance, an organisation or a political system. This cybernetic agency theory is connected to Bandura's theory of psychosocial function. The agency is adaptive and has a normative personality that operates through three formative personality traits, the function of which is control. The cybernetic agency theory is presented as a meta‐model, which comes from cybernetic "living systems" theory. Design/methodology/approach – First, in this paper, the authors discuss the virtues of a normative cybernetic agency model in the light of issues related to normal states and pathologies of systems. Formative traits could be derived from Maruyama's mindscape theory or Harvey's typology. However, Boje has noted that with four mindscape types Maruyama's typology is constrained. Consequently, he projected the Maruyama mindscapes into a space with the three Foucault‐dimensions: knowledge, ethics and power. Findings – The suggested cybernetic agency model with the three formative personality traits can provide a framing for a structural model that has the potential to distinguish between normal and abnormal personalities in the same framework. Research limitations/implications – The constraints of the Maruyama mindscape space, as identified by Boje, are suggesting that further research is needed to identify a formative three‐trait‐system which is theory based, was empirically applied, and is permitting to create a typology with eight extreme types, yet to be identified. Originality/value – The paper draws on earlier work undertaken in the last few years by the same authors, who in a new way are pursuing new directions and extensions of that earlier research.